Rutaecarpine Attenuates Oxidative Stress-Induced Traumatic Brain Injury and Reduces Secondary Injury via the PGK1/KEAP1/NRF2 Signaling Pathway - Xu, Min; Li, Liu; Liu, Hua; Lu, Wei; Ling, Xiaoyang; Gong, Mingjie (Frontiers in Pharmacology, 2022)
Abstract: The oxidative stress response caused by traumatic brain injury (TBI) leads to secondary damage in the form of tissue damage and cell death. Nuclear transcription-related factor 2 (NRF2) is a key factor in the body against oxidative stress and has an important role in combating oxidative damage in TBI neurons. In the present study, we investigated whether rutaecarpine could activate the PGK1/KEAP1/NRF2 pathway to antagonize oxidative damage in TBI neurons. We performed controlled cortical impact (CCI) surgery on mice and taken H2O2 treatment on PC12 cells to construct TBI models. The results of western blot showed that the expression of PGK1, KEAP and NRF2 was regulated and accompanied by altered levels of oxidative stress, and the use of rutaecarpine in the TBI model mice significantly improved cognitive dysfunction, increased antioxidant capacity and reduced apoptosis in brain tissue. Similar antioxidant damage results were obtained using rutaecarpine in a PC12 cell model. Furthermore, through the use of the protein synthesis inhibitor CHX and the proteasome synthesis inhibitor MG-132, rutaecarpine was found to promote the expreesions of PGK1 and NRF2 by accelerating PGK1 ubiquitination to reduce PGK1 expression. Therefore, rutaecarpine may be a promising therapeutic agent for the treatment of TBI-related neuro-oxidative damage.